Yogyakarta Muslim Student Resilience Profile - Amien Wahyudi; Siti Partini; Shopyan Jepri Kurniawan (International Conference on Science, Education, and Technology, 2022)
Muslim students in Yogyakarta are the majority of students who are the successors of the next generation of Islam. For this reason, Muslim students need to have good self-resilience. The purpose of this study was to determine the level of resilience of Muslim students in Yogyakarta. Used quantitative approach and descriptive analysis design used quantitative approach and descriptive analysis design to answer research questions—data obtained from 369 students at the Islamic School in Yogyakarta. The data collection instrument used a 10-item Connor-Davidson Resilience Scale (CD-RISC). The results showed that as many as 178 Muslim students or 48% were in the high resilience category, 178 Muslim students, or 48%, were in the moderate resilience category, and 13 Muslim students, or 4%, were in the low resilience category. Discussion, limitations, and suggestions are also described in this paper.